Bedside resuscitation of newborns with an intact umbilical cord: Experiences of midwives from British Columbia. (March 2016) - Fulton, Colleen; Stoll, Kathrin; Thordarson, Dana
Abstract: Context: level 1 evidence supports the practice of delayed cord clamping, and many doctors and midwives consider it routine care when delivering vigorous, term neonates. However, scarce research exists regarding the risks or benefits of delayed cord clamping for infants needing resuscitation with positive pressure ventilation. Nonetheless, some midwives in British Columbia already practice intact cord resuscitation (ICR) at planned home births and in the hospital in order to facilitate delayed cord clamping for infants who need resuscitation. Methods: we distributed an online survey to all registered midwives in British Columbia through the Midwives Association of BC between October 22nd and November 13th, 2014. This survey examined how midwives balance a commitment to delayed cord clamping with the need for resuscitation in home and hospital settings. Findings: a total of 82 midwives responded to the survey (response rate=35%). Many have practiced ICR (56, 69%). However, the majority (42, 78%) of respondents had only performed this type of resuscitation at planned home births and not in the hospital setting. In both settings, midwives found the ergonomics of resuscitation with an intact cord challenging, but cited a smoother physiologic transition for neonates as their primary reasons for this practice, despite the obstacles. Midwives reported a greater ability to use their delivery equipment to provide stable thermoregulation at the bedside at planned home births during a resuscitation compared with the set up of hospital delivery rooms. Conclusion: although the majority of participants practice ICR at planned home births, very few use this practice in the hospital setting. In the home, ergonomics is the primary obstacle for easily practicing ICR; hospital culture, protocols and lack of training are additional barriers to this practice in the hospital setting. Ergonomics and lack of appropriate set up in the delivery room were also primary obstacles. Midwives expressed a desire to find ways to incorporate ICR into the hospital setting. Highlights: ICR is currently practiced by many BC midwives, mostly at planned home births. Hospital culture and ergonomics are the primary obstacles to practicing ICR at hospital births. Most respondents report ICR enables delayed cord clamping and a smoother transition for infants. Further research in this area is needed.